Effect of Talent Management Practices on Employees Personal Growth in Private Hospitals in Benghazi, Libya - Alferjany M.A.O.A.; Alenzi M.A.S.; Alias R.B. (Tarbiat Modares University, 2023)
Aims The present study aimed to examine the effect of talent management (talent attraction, talent retention, talent development) on the personal growth of employees (growth mindset, metacognition, and self-authorship) in private hospitals in Benghazi, Libya. Instruments & Methods This descriptive-analytical study was conducted in July 2022 using a questionnaire that was specifically designed for this purpose and had 29 paragraphs on a fivepoint Likert scale. The studied population consisted of the upper and middle managers of 5 private hospitals in Benghazi. 255 employees were selected to form a stratified random sample from the studied population with a response rate of 90.16%. Regression analysis was used to evaluate the effect of the independent variable on the dependent variable. Findings A high level of application was observed for talent management, while the application of personal development was low. Also, the effect of talent management on individual growth was significant with ?=0.720. Conclusion Talent management practices affect positively employees personal growth in private hospitals in Benghazi, Libya. 2022, the Authors | Publishing Rights, ASPI.